2001
DOI: 10.1248/cpb.49.64
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Water Dispersion Conditions and Pressure Transmission Characteristics of a Wet Kneaded Mass.

Abstract: Kneading of powdered materials [1][2][3] has been widely used in the pharmaceutical, agriculture, food, chemical, forage and fertilizer industries. Most of the cases, kneading is conducted before the granulation and molding processes, and the performance of kneading seriously affects the quality of the final product or process efficiency. Therefore, it is very important to quantitatively monitor kneading conditions during the kneading operation. With the present technical levels, however, most operations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…After the kneading, the kneaded wet-mass powder was extruded through an extrusion granulator (DG-L1, Fuji Paudal, Co., Ltd.), which consisted of a hemispherical dorm type punching screen (diameter of the dome was 58 mm, diameter of each hole and width of the screen were both 0.8 mm, and the opening area ratio was 22.5%), a single shaft with screws and an extrusion blade at the extremity of the shaft. 1,8) The dry product (pellets) was finally obtained after a fluidized bed drying (NQ-125, Fuji Paudal, Co. Ltd.) 9) of wet extruded pellets under the air temperature of 353 K. Physical properties of the dried pellets were evaluated by their strength and dissolution time (the method for measuring the granule strength and dissolution time was the same as previously reported 1) ).…”
mentioning
confidence: 99%
“…After the kneading, the kneaded wet-mass powder was extruded through an extrusion granulator (DG-L1, Fuji Paudal, Co., Ltd.), which consisted of a hemispherical dorm type punching screen (diameter of the dome was 58 mm, diameter of each hole and width of the screen were both 0.8 mm, and the opening area ratio was 22.5%), a single shaft with screws and an extrusion blade at the extremity of the shaft. 1,8) The dry product (pellets) was finally obtained after a fluidized bed drying (NQ-125, Fuji Paudal, Co. Ltd.) 9) of wet extruded pellets under the air temperature of 353 K. Physical properties of the dried pellets were evaluated by their strength and dissolution time (the method for measuring the granule strength and dissolution time was the same as previously reported 1) ).…”
mentioning
confidence: 99%
“…The decrease in the standard deviations of moisture content means that water is more uniformly dispersed among the wet kneaded mass with the elapsed time of rotating blade accompanied with shear of stress. Watano et al [11][12][13] also reported the improvement of uniform water dispersion during the kneading process, and Evrard et al 16) reported the evolution of the product temperature during the melt granulation process in the high-shear mixer. The findings shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Watano et al [11][12][13] have recently demonstrated that properties of the wet kneaded mass are directly characterized by internal pressure transmissions which are determined by using a newly developed compression tester instead of the torque rheometry. Furthermore, it was also documented that the pressure transmissions were strongly associated with water dispersion among the wet kneaded mass.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…11) Watano et al evaluated the water dispersion of a wet kneaded mass using a compression test and predicted the properties of the final extruded products. 12) They also analyzed the rheo-mechanical properties of wet powder. 13,14) Meanwhile, several studies on the prediction of optimal formulations have been made.…”
mentioning
confidence: 99%